What Almost Was: The Politics of the Contemporary Alternate History Novel - Schneider-Mayerson, Matthew (American Studies, 2009)
The alternate history novel, a genre of American popular fiction that has become increasingly popular since the mid-1990s, has flown under the critical radar. In this paper, I contextualize the emergence of the genre, identify its common properties, and closely analyze several texts. I argue that the development of the alternate history can be tied to the end of the cold war and the loosening grip of deterministic ideologies; by comparing the internal worlds of alternate histories with the site of their production, I suggest that the underlying militaristic, anti-“big government” tone of the genre reflects the power of libertarian ideas in the contemporary United States.